Sustainability and the Thoroughbred breeding and racing industries: an enhanced one welfare perspective - Stallones, Lorann, author; McManus, Phil, author; McGreevy, Paul, author; MDPI, publisher (Colorado State University. Libraries, 2023)
As society debates the use of animals in sport, entertainment, and leisure, there is an increasing focus on the welfare, social, and ecological impacts of such activities on the animals, human participants, people close to them, and the physical environment. This article introduces the "Enhanced One Welfare Framework" to reveal significant costs and benefits associated with Thoroughbred breeding and racing globally. In addition, relative to calls to ban horseracing and similar activities as part of sustainability approaches that focus chiefly on animals, the "Enhanced One Welfare Framework" is better positioned politically to guide discussions that renegotiate the conditions under which horses are used for sport and the impact racing has on humans and the planet. In 2020, the International Federation of Horseracing Authorities issued its minimum horse welfare standards based on the Five Domains model, positioning lifelong horse welfare as "fundamentally important to the viability and sustainability of the industry". In this article, we critique the One Welfare framework's historic lack of focus on sport and enhance it by including sport, leisure, and entertainment and framing it within the Five Domains model. We offer a novel extension of the Five Domains model beyond animal welfare to consider human welfare and the physical environmental impacts of the sport, leisure, and entertainment industries and propose innovations that may help thoroughbred breeding and racing assure a sustainable future.
Keywords: horseracing; welfare; safety; climate change; social license to operate